THE SALARY AND CASH DISBURSEMENT ACCOUNTING SYSTEM IN OTHER TO SUPPORT THE INTERNAL CONTROL (Study at Perusahaan Daerah Air Minum (PDAM)Tirta Dharma, Situbondo) - Dewi Ayu Lazuardi (Fakultas Ilmu Administrasi Universitas Brawijaya, 2014)
The Salary and Cash Disbursement Accounting System based on necessity of application of internal control because the application of internal control for salary disbursement is very important for all companies that want to create the effective procedures for increasing the internal control aims. At PDAM Tirta Dharma with the focus on Salary and Cash Disbursement Accounting System thus obtained proof that there are still weaknesses in the procedures of salary disbursement. There is the overlapping function in organization structure. Redesigning the salary disbursement procedures which stressing on the function separation between General Affair. Separation function in organization structure is must. Keywords: Salary Disbursement, Internal Control, Overlapping Function ABSTRAK Prosedur Pengeluaran Kas dan Gaji yang didasari atas perlunya aplikasi sistem pengendalian intern gaji dalam rangka meningkatkan kinerja pada PDAM Tirta Dharma. pada PDAM Tirta Dharma dengan fokus pengeluaran gaji dalam mendukung pengendalian intern maka diperoleh bukti bahwa masih terdapat kelemahan pada sistem gaji di PDAM Tirta Dharma dan terdapat prosedur perangkapan fungsi di bagian anggaran merangkap banyak fungsi. Situasi ini jika berlanjut terus akan melemahkan pengendalian intern. peneliti sarankan seyogyanya mendesain kembali struktur organisasi yang menekankan pemisahan fungsi untuk akuntansi, operasional, dan keuangan dan diefektifkan personel-personel yang ada untuk mampu didayagunakan perusahaan dalam melaksanakan fungsi sesuai dengan pengendalian intern. Kata kunci: Pengeluaran Gaji, Pengendalian Intern, Perangkapan Fungsi